2015
DOI: 10.1093/ajh/hpv153
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Hypertension Remission and Recurrence After Bariatric Surgery

Abstract: HTN relapses in 1 of 5 hypertensives who have achieved remission at the first year of follow-up. Weight loss during the first postoperative year should be encouraged to avoid HTN relapse at 3 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 36 publications
6
29
0
2
Order By: Relevance
“…These molecules were shown to Hypertension Remission contribute to vascular stiffness, which can favour hypertension development and poor CV outcome. 32,33 Unfortunately, we did not perform a long-term follow-up to confirm this finding. 24 Our results may be judged as "paradoxical," since we previously demonstrated that high baseline hs-CRP predicts good clinical response to bariatric surgery in terms of diabetes remission and reduction in visceral fat.…”
Section: Discussionmentioning
confidence: 88%
“…These molecules were shown to Hypertension Remission contribute to vascular stiffness, which can favour hypertension development and poor CV outcome. 32,33 Unfortunately, we did not perform a long-term follow-up to confirm this finding. 24 Our results may be judged as "paradoxical," since we previously demonstrated that high baseline hs-CRP predicts good clinical response to bariatric surgery in terms of diabetes remission and reduction in visceral fat.…”
Section: Discussionmentioning
confidence: 88%
“…Although a comprehensive discussion on bariatric surgery is beyond the scope of our review, we need to mention that it might become an appropriate treatment option for some patients. Commonly used bariatric procedures include gastric banding, Roux-en-Y gastric bypass, and sleeve gastrectomy [124][125][126][127][128] . On average, weight loss with bariatric surgery is greater than with nonsurgical interventions, around 15-35% depending on the procedure [120,[129][130][131][132] .…”
Section: Traditional Approachmentioning
confidence: 99%
“…Although bariatric surgery may result in greater weight loss than other obesity interventions, it is an invasive procedure that requires important long-term commitment and follow-up by patients and health-care teams. Consequently, current treatment recommendations reserve bariatric surgery for people with BMI ≥ 40 or ≥ 35 with obesity-associated complications [120,[126][127][128][133][134][135] . Those who are interested in further updating their knowledge on current alternatives for obesity treatment will find a recent review to be a great help [121,136] .…”
Section: Traditional Approachmentioning
confidence: 99%
“…Both procedures proved equally effective in the resolution of comorbidities and the weight loss. 13 This change, both in weight and comorbidities, directly impacts mortality, with a decrease between 29 and 40% and with improvements in terms of life expectancy. 14 We know that obesity accounts for between 2 and 7% of the overall health costs of a country, which can translate, in the USA, into 100 billions of dollars each year.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] A Swedish study showed more benefits with the bypass, although it is worth mentioning that this study did not include the gastric sleeve. 13 Bariatric surgery has proved to be the most effective treatment in management of metabolic syndrome. 25 A decrease of more than 50% of the patient's excess weight has a significant impact on the resolution of this pathology and the type of surgery undertaken does not affect this result; in our cohort, there was a loss of 30% of the patient's excess weight in the 1st month, leading to a significant improvement of their metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%